The Influence of School Principal Leadership and Work Discipline on Performance - Heru Sriyono (Riviera Publishing, 2024)
This study aims to analyze the effect of principal leadership and work discipline on teacher performance in private vocational schools in South Jakarta. The research method used is a survey method with multiple correlational regression techniques, involving 80 teachers as samples. The results showed that there is a significant influence of the principal's leadership and work discipline together on the performance of teachers in private vocational schools in South Jakarta (Sig. = 0.000 <0.05, F Count = 11.295). In addition, there is a significant effect of principal leadership on teacher performance (Sig. = 0.000 < 0.04, T = 2.931) and a significant effect of work discipline on teacher performance (Sig = 0.037 < 0.05, T = 2.115). The implication of this study is the important role of principal leadership and work discipline in improving teacher performance in private vocational schools. This provides a clear picture for education practitioners and policy makers about the need for effective leadership development and consistent application of work discipline in schools. Thus, it is expected to create a more productive and quality educational environment for students, teachers and all education stakeholders in South Jakarta.